The Nature and characteristics of the major Kurdish movements: an analysis of Kurdish movements from the Bedirhan Rebellion (1847) to the Sheikh Said Rebellion (1925) - Sözbir, Hacer. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
This work evaluates the important Kurdish rebellions, which are the Bedirhan Rebellion (1847), the Sheikh Ubeydullah Rebellion (1880), the Koçgiri Rebellion (1921) and the Sheikh Said Rebellion (1925). While the first three of the rebellions took place during the Ottoman era, the last one, the Sheikh Said rebellion broke outin republican Turkey. The aim of this work is to introduce the continuity and differentiation in the Kurdish rebellions; nevertheless, it does not attempt to explainthe history of Kurdish nationalism inasmuch as nationalism constitutes only one aspect of the latter two rebellions mentioned above. The centralization attempts of the state that started from the Tanzimat periodand continued into the republican era were a major threat to the local Kurdish aghasand sheikhs. The Bedirhan rebellion and the Sheikh Ubeydullah rebellion were typical examples of resistance against the centralization of the Ottoman state, and they broke out in order to preserve old prerogatives and expand the authority of the tribal leaders over Ottoman Kurdistan. In spite of the changing slogans and the diversity of the participants, the local Kurdish leaders were the main actors of the Koçgiri rebellion and the Sheikh Said rebellion, since any government intervention or centralization endeavor was a challenge to their authority. However, anationalistic dimension was added to the Kurdish movement in the twentieth century. This new dimension stemmed from the educated Kurds, who evolved fromself-awareness to nationalism and participated in the Koçgiri and Sheikh Said rebellions. Nevertheless, it would be misleading to refer one or two reasons and torely exclusively on the nationalist discourse with respect to the Kurdish movements.Being aware of this reality, this thesis discusses the issue within a larger context of the Tanzimat, the Hamidian period, and the republican era.
Keywords: Kurds -- Turkey -- History.